(untitled) (Anuario Filosófico, 2018)
The way Aristotle conceives his very notion of potency manifests that capacity and incapacity are not as far from each other as we usually think, the reason for that being the finite character of potency on the one hand and the presence of télos in the heart of potency on the other hand.